Factors Affecting Catalase Expression in Pseudomonas aeruginosa Biofilms and Planktonic Cells - Frederick, Jesse R. (American Society for Microbiology, 2001)
Previous work with Pseudomonas aeruginosa showed that catalase activity in biofilms was significantly reduced relative to that in planktonic cells. To better understand biofilm physiology, we examined possible explanations for the differential expression of catalase in cells cultured in these two different conditions. For maximal catalase activity, biofilm cells required significantly more iron (25 μM as FeCl(3)) in the medium, whereas planktonic cultures required no addition of iron. However, iron-stimulated catalase activity in biofilms was still only about one-third that in planktonic cells. Oxygen effects on catalase activity were also investigated. Nitrate-respiring planktonic cultures produced approximately twice as much catalase activity as aerobic cultures grown in the presence of nitrate; the nitrate stimulation effect could also be demonstrated in biofilms. Cultures fermenting arginine had reduced catalase levels; however, catalase repression was also observed in aerobic cultures grown in the presence of arginine. It was concluded that iron availability, but not oxygen availability, is a major factor affecting catalase expression in biofilms.